The Institutional Dynamics of Sub-District in Indonesia - Utomo, Sad Dian; Ridwan Maksum, Irfan; Kurniawan, Teguh (Technium Social Sciences Journal, 2023)
This article examines what factors lead to the institutional dynamics of sub-district in Indonesia. Institutional dynamics are changes due to interaction patterns, values, culture, and people’s tastes. In this study, we look at the institutional dynamics of sub-district from two primary causal factors: endogenous and exogenous. The findings conclude that endogenous factors consist of the sub-district human resources, budget, and creativity/innovation of the sub-district head. In comparison, exogenous factors consist of national policies related to sub-districts; the role of the sub-district supervisor; regent/mayor commitment; public perception; information technology; and area characteristics (rural and urban). Based on these institutional dynamics, it is necessary to reposition sub-district institutions by developing sub-district institutional models for rural areas, urban areas, and a hybrid of both.